Bobby Bear's Sticker Book - Wood, A J (The Advantage Publishers Group, 1999)
Inside,you will find over 150 stickers.Use them to make your own pictures as you explore the field and forest with Bobby and his animal friends.
Keywords: Juvenile literature-Fiction